(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
Now, innovative activity is key for domestic companies, it is necessary to develop the scientific and technical base, participate in scientific developments, but the crisis time, sanctions and a period of uncertainty brings its adjustments to the plans of scientists and organizations. The purpose of the study is to analyze the innovation market, analyze innovation activity in Russia and analyze scientific materials in order to identify the importance of innovative developments for organizations. Now innovation is very important for companies, but their development is complicated by global trends, the activity of innovative developments is decreasing, and these dynamics will continue. The scientific community and organizations need to unite in order, due to the synergistic effect, to increase the efficiency of activities in the field of innovative development, to reach the pre-crisis indicators of activity, and possibly in some cases record growth above the indicators before the crisis.